2011
DOI: 10.1109/tpel.2010.2052633
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Sinusoidal Input-Current Shaping of 12-Pulse Autotransformer Rectifier Unit With Impressed Output Voltage

Abstract: This paper presents a novel closed-loop currentcontrol strategy for a hybrid 12-pulse rectifier that uses a twoswitch boost stage for output-voltage regulation. Unlike previous attempts to mitigate input-current distortion, e.g., by modulating the rectifier output voltage with open-loop control, this new closed-loop current-control scheme directly controls the lineinterphase-transformer input voltage and/or impresses sinusoidal input currents. In this paper, the control strategy is explained and the modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The 12-pulse diode bridge rectifiers are extensively proposed for more electric aircraft applications [30][31][32][33][34]. Assuming the current flow through TRU be continuous and the semiconductor diodes used in full-bridge rectifier are ideal, then Fig.…”
Section: Non-linear Description Of Tru With Low Pass Filter (Lpf)mentioning
confidence: 99%
“…The 12-pulse diode bridge rectifiers are extensively proposed for more electric aircraft applications [30][31][32][33][34]. Assuming the current flow through TRU be continuous and the semiconductor diodes used in full-bridge rectifier are ideal, then Fig.…”
Section: Non-linear Description Of Tru With Low Pass Filter (Lpf)mentioning
confidence: 99%
“…Since the three-phase buck-type PWM converter will generate a DC output voltage, o α is fixed and equal to 0; hence (1) can be simplified to (3), while (2) can be simplified to (4). …”
Section: A the Modualtion Strategymentioning
confidence: 99%
“…The main advantage of this topology is its high reliability. However it has a number of disadvantages such as distorted input currents, uncontrolled output voltage and high weight due the presence of the autotransformer and of an inter-phase reactor [4]. Recent studies [5] have shown that a better solution for this application in terms of high reliability and low weight is the use of a 3-phase buck-type PWM rectifier [6]-[10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have explored a variety of methods to reduce the input line current distortion of diode recti ers in recent decades . Compared with other harmonic reduction methods, because of the small kilo-Volt Ampere (kVA) rating of auxiliary current injection circuit and excellent harmonic reduction ability, the method of active harmonic reduction at dc side is suitable for high power applications and has drawn more and more attention [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%